A Study of Electronic Dalaw Implemented by the Bureau of Jail Management and Penology in Caloocan City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
During the pandemic in Caloocan City Jail, the electronic dalaw service is an alternative to the traditional face-to-face visitation between PDL and respective families. Implementing E-Dalaw helped Bilibid prisoners communicate with their families during their incarceration. This reformation program acted as a way for inmates to strengthen relations with family locally or abroad through video calls upon their release from prison. Resuello and Tatlonghari surveyed the users of e-dalaw and gained positive feedback, suggesting overall satisfaction in using the system.This study uses a descriptive method of research with correlation analysis. The researchers conducted quantitative research since the study deals with statistical measurements and the best approach for the study.The researchers interviewed the PDL and Jail officers inside Caloocan City Jail using a survey questionnaire to gather information from the respondents.The study concluded that based on the demographic profile of the two groups of respondents' PDL and Jail officers at Caloocan City Jail, the majority of the respondents were 50 and above. Most were at the high school level with a frequency of 9, equivalent to 18 percent each.The study's findings show the implementation, scope, and limitations of the e-dalaw implemented in Caloocan City Jail. As attested by the group respondents on the perception of the opportunities given, Caloocan City Jail must provide a stable connection to the internet, computer, and e-tawag for PDL and Jail Officers so they have easy access to their loved ones. And monitor and minimize the risk of smuggling illegal contraband. The effectiveness of the e-dalaw implemented in Caloocan City Jail, PDL overcame their longingness with their family following the e-dalaw implementation. The effectiveness of the finding lessened the risk of violating health protocols and the risk of smuggling illegal activities.